(untitled) (Fiep Bulletin - online, 2013)
This article is the result of an undergraduate research project - PIC / FISJT which sought to investigate whether motor age corresponded to chronological age in children entering in two different types of schools - one public and the other private. It was used as a tool for collecting a battery of tests of Motor Development Scale (EDM), proposed by Rosa Neto (2002), covering seven dimensions of human movement: fine motor (IM1), gross motor control (IM2), balance (IM3), body schema (IM4), spatial organization (IM5), temporal organization (IM6), and laterality, which was not used in the study because it used a different methodology. Each test contains five tasks that will gradually become more complex. Scores are measured in months to determine the motor age. It was concluded in the study that the final values ??of the motor ratio, the motor ages and corresponding diagnostic category among schoolchildren showed the age gap between motor (IM) and chronological age (CA) six years showing the classification of the skills assessed in the public school network standards: much lower, lower, normal and low normal average. In private: low normal, normal medium, lower and much lower. There was a greater gap in public school, probably due to lack of stimulation of the students by teachers. In this network there is no separate physical education teacher. It is the same teacher educator, unlike the private school network where there is a physical education expert teacher.